2022
DOI: 10.1002/ar.25021
|View full text |Cite
|
Sign up to set email alerts
|

Rare juvenile material constrains estimation of skeletal allometry in Gryposaurus notabilis (Dinosauria: Hadrosauridae)

Abstract: In studying the skeletal allometry of any vertebrate, it is important to sample the ontogenetic extremes to ensure the accuracy of parameter estimation; this is particularly true for fossil taxa, where sampling of ontogenetic series is incomplete and sporadic. Previous studies have examined allometry in the skull of the duck-billed dinosaur Gryposaurus notabilis, but these did not include individuals smaller than $65% the maximum known size (based on linear dimensions). Here, we report on the two smallest know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…Although a two‐dimensional view of the suture surface does not capture complete information on the three‐dimensional suture face, isolated calvarial bones in iguanodontians show that they are fairly consistent in suture interdigitation along these sutural contacts, and studying the suture surface is, therefore, a good approximation of suture shape. Gryposaurus specimens were identified as species following Lowi‐Merri and Evans (2020) and Mallon et al (2022). Isolated lambeosaurine braincases from Dinosaur Park were tentatively identified by us as Lambeosaurus if the frontal‐nasal suture formed a raised ridge, and as Corythosaurus if this ridge was absent.…”
Section: Methodsmentioning
confidence: 99%
“…Although a two‐dimensional view of the suture surface does not capture complete information on the three‐dimensional suture face, isolated calvarial bones in iguanodontians show that they are fairly consistent in suture interdigitation along these sutural contacts, and studying the suture surface is, therefore, a good approximation of suture shape. Gryposaurus specimens were identified as species following Lowi‐Merri and Evans (2020) and Mallon et al (2022). Isolated lambeosaurine braincases from Dinosaur Park were tentatively identified by us as Lambeosaurus if the frontal‐nasal suture formed a raised ridge, and as Corythosaurus if this ridge was absent.…”
Section: Methodsmentioning
confidence: 99%
“…The same is true for Saurolophinae, for example, in Gryposaurus notabilis (juvenile ROM 1939 with 25 tooth families (Mallon et al . 2022); large individuals with up to 40 (Lull & Wright 1942)) and Edmontosaurus annectens (juvenile UCMP 235860 with 9 tooth families, and subadult ROM 73859 with 44 (Wosik et al . 2019); adult specimens with up to 55 (Prieto‐Márquez 2008, p. 263)).…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that the ceratobranchial, basihyal, cricoid, and paraglossal are likely keys in archosaur hyolaryngeal evolution (Yoshida et al, 2023). Mallon et al (2023) examined the smallest known examples of Gryposaurus notabilis that either reinforce or shed new light on developmental growth and biomechanics within the hadrosaurs. Previous studies did not include individuals smaller than 65% of the maximum known adult size.…”
mentioning
confidence: 99%
“…Mallon et al (2023) examined the smallest known examples of Gryposaurus notabilis that either reinforce or shed new light on developmental growth and biomechanics within the hadrosaurs. Previous studies did not include individuals smaller than ~65% of the maximum known adult size.…”
mentioning
confidence: 99%
See 1 more Smart Citation